Relationships between food quality and fitness in the desert locust, Schistocerca gregaria, and its distribution over habitats on the Red Sea coastal plain of Sudan - Huis, A. van; Woldewahid, G.; Toleubayev, K.; Werf, W. van der (Wiley, 2008)
The effect of millet, Pennisetum typhoideum Rich. (Poaceae), leaf nitrogen content on fitness parameters of the desert locust, Schistocerca gregaria Forsk. (Orthoptera: Acrididae), was studied under laboratory conditions. Locusts reared on high-nitrogen leaves were larger, developed faster, had higher survival, reproduced more and earlier, and showed greater synchronization than those fed on low-nitrogen leaves. Active and passive cannibalism contributed to mortality when locusts were reared on low-nitrogen leaves, but not when reared on high-nitrogen leaves. Elevated leaf nitrogen content of host plants increased net reproduction and intrinsic rate of increase, and lowered generation time. The findings show that nitrogen content of host plants affects the potential for population increase in the desert locust. Leaf samples of common plant species were collected in the Heliotropium arbainense (Fresen.) (Boraginaceae) and Panicum turgidum (Forssk.) (Poaceae) plant communities on the Red Sea coastal plain of Sudan during the winters of 1999 and 2000. The levels of leaf nitrogen in host plants were comparable to those in the laboratory studies and consistently higher in plant samples from the Heliotropium community than in samples from the Panicum community. Both in 1999 and 2000, locust densities were much higher in the Heliotropium than in the Panicum plant community. It should be assessed whether the desert locust would be attracted to sites where host plants have high leaf nitrogen content, as this would not only increase their fitness, but also the likelihood of gregarization and outbreaks.